Preparation of a solid acid derived from Japanese cedar sawdust and evaluation of its the catalytic activity - Toshiyuki Miyauchi; Yui Igaki; Ryoya Murata; Sumire Tanabe; Masaki Tsujimoto; Yuko Shikami (Journal of Wood Science)
Abstract The preparation of a solid acid by chemical treatment of plant-derived biomass has been explored, along with an evaluation of its catalytic activity. The solid acid was prepared by pretreating Japanese cedar sawdust with hydrochloric acid, followed by sulfonation using sulfuric acid and fuming sulfuric acid. Surface analysis using energy-dispersive X-ray spectroscopy confirmed the presence of sulfur atoms on the surface, while X-ray photoelectron spectroscopy demonstrated the introduction of sulfo groups into lignin, forming a plant-derived biomass. A pH titration using NaOH revealed an acidity of 2.25 mmol g–1, indicating that Japanese cedar sawdust can function as an acid following chemical treatment. Therefore, the use of solid acids as catalysts for esterification reactions, as an alternative to mineral acids, was investigated. Specifically, the reaction between acetic acid and ethanol to form ethyl acetate proceeded at room temperature, reaching chemical equilibrium within 570 min following the addition of the solid acid catalyst. The reaction rate increased with temperature, and the catalyst maintained high activity even at high temperatures. Although heterogeneous catalysts, such as solid acids have low contact efficiencies, they can still catalyze esterification reactions, similarly to mineral acids. Furthermore, solid acids exhibit greater catalytic capacity at elevated temperatures, while also being recyclable. Overall, this study presents a novel application of unused biomass in catalysis, demonstrating its potential as a sustainable catalyst.